Editor’s Letter - Flores, Dora-Luz (Revista Mexicana de Ingenieria Biomedica, 2022)
It is a great honor and pleasure to present this issue of theRevistaMexicanadeIngenieríaBiomédica RMIB. This 2022 edition of RMIB brings even more pioneering research content from Mexico and Latin America in the broad area of Biomedical Engineering. Despite continu- ing to live in a pandemic caused by covid-19, the RMIB continues to show results from the authors who decide to take this journal as their option for publication.